Improving Governance in Major Infrastructure Projects - Phalguni Sundaram Biswal (Journal of Infrastructure Policy and Management (JIPM), 2021)
From an economic growth perspective, infrastructure is not only an enabling factor for development or for facilitating private investments and competitiveness across all sectors of national and regional economies, but can also be an attractive investment opportunity in itself. Although infrastructure investment opportunities are plentiful across developing countries, investors are not fully seizing them, often due to gaps in the enabling environment for such investment. The infrastructure sector presents specific risks to private investors, and since private participation in infrastructure delivery is a relatively recent form of procurement in many countries, governments do not necessarily have the experience and capacity needed to effectively manage these risks. Beyond case-by-case project preparation and financing, concrete, implementation-oriented guidance that can help governments identify and manage reforms is needed to make the broader infrastructure investment environment more open to private participation.